Preparation method of supported high-entropy pt-based catalyst and application of the catalyst in preparation of propylene from propane dehydrogenation

CN117920264BActive Publication Date: 2026-10-27DALIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410034461.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-10
Publication Date
2026-10-27
Estimated Expiration
2044-01-10

AI Technical Summary

Technical Problem

但是催化剂在高温反应及后续氧化再生中仍不可避免的发生烧结,进而导致催化剂失活

Benefits of technology

[0025]本发明将Pt、Zn、Mn与至少两种非贵金属元素负载在载体上,实现高熵材料的纳米化,可大大的提高活性相的暴露程度,并抑制裂解、氢解、积碳等副反应的发生,适用于催化领域。具体如下:能够提高高熵金属粒子的分散度,以此提高贵金属的利用率;提高纳米金属粒子在高温下的热稳定性;强化金属催化剂的催化活性和催化剂稳定性;特别是在高温反应中表现出独特的稳定性;所适用的金属元素和金属前驱体涉及广泛;该方法制得的高熵催化剂与一般非高熵催化剂相比在丙烷脱氢反应中表现出了高转化率、高选择性和催化稳定性。采用高熵催化剂实现对Pt物种的稳定,相比现行的分子筛封装限域、在载体上创造缺陷锚定Pt物种等方式具有制备工艺简单、价格低廉等优势。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117920264B_ABST
    Figure CN117920264B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a supported high-entropy Pt-based catalyst and application of the catalyst in preparation of propylene from propane dehydrogenation, the catalyst comprising a carrier and a metal active component, the metal active component comprising Pt elements, Zn elements, Mn elements and A metal elements, the A metal elements being at least two of Fe, Co, Ni, Cu, Ga, Ge, In and Sn; the mass percentage of Pt in the catalyst being 0.1-3 wt.%; and the catalyst being obtained by impregnating a carrier with a metal precursor salt solution, drying, calcining and reducing. The Pt, Zn, Mn and A metal are supported on the carrier to realize nanocrystallization of the high-entropy material, and the catalyst exhibits high conversion rate, high selectivity and catalytic stability in the propane dehydrogenation reaction, and has excellent regeneration cycle stability. In addition, the high-entropy catalyst is used to stabilize Pt species, and has the advantages of simple preparation process and low price compared with the current methods of encapsulating and limiting Pt species by molecular sieves, creating defects on the carrier to anchor Pt species and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of propane dehydrogenation to propylene technology, specifically to a method for preparing a supported high-entropy Pt-based catalyst and its application in propane dehydrogenation to propylene. Background Technology

[0002] Propylene is a key raw material for the production of various products such as polypropylene, propylene oxide, and acrylonitrile. Traditionally, propylene is produced through the thermal cracking or catalytic cracking of naphtha derived from crude oil. However, in recent years, the global shortage of oil resources has led to insufficient propylene supply. Simultaneously, with the continuous extraction of natural gas and shale gas, which contain large amounts of alkanes, the dehydrogenation of alkane to produce propylene can not only alleviate pressure on oil resources but also meet market demand. Therefore, propane dehydrogenation to propylene has attracted considerable attention among various processes.

[0003] The Oleflex and Catofin processes are the dominant propane dehydrogenation processes, primarily using PtSn / Al₂O₃ and Cr₂O₃ / Al₂O₃ catalysts, respectively. The noble metal Pt possesses excellent propane activation capabilities. Because propane dehydrogenation is thermodynamically balanced, high temperatures favor the reaction; however, at high temperatures, Pt catalysts are prone to coking and sintering, leading to irreversible deactivation. Current research largely addresses this by adding secondary promoters such as Sn, Zn, Ga, and Cu. These methods aim to dilute large Pt particles to smaller particles or even single-point Pt, suppressing structure-sensitive side reactions (coking). They also adjust the electronic structure of Pt to reduce its propylene adsorption capacity and inhibit the formation of coking precursors. However, sintering is still unavoidable during high-temperature reactions and subsequent oxidation regeneration, ultimately leading to catalyst deactivation. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing and applying a supported high-entropy Pt catalyst. The supported high-entropy Pt-based catalyst prepared by this method is a high-entropy nanoparticle containing five or more metal elements, which has good structural stability and excellent propane dehydrogenation performance, and effectively improves the stability of the catalyst in high-temperature reactions.

[0005] This invention proposes a method for preparing a supported high-entropy Pt catalyst, wherein the supported high-entropy Pt catalyst comprises a support and a metal active component, wherein the metal active component comprises Pt, Zn, Mn and Al, wherein the Al is at least two of Fe, Co, Ni, Cu, Ga, Ge, In and Sn; the mass percentage of Pt in the catalyst is 0.1-3 wt.%.

[0006] The preparation method includes the following steps:

[0007] S1 mixes the metal precursor salt and the solvent to obtain a metal precursor salt solution;

[0008] S2 uses a co-impregnation or stepwise impregnation method to impregnate the metal precursor salt onto a carrier to obtain a mixture;

[0009] S3 is subjected to drying, calcination and reduction of the mixture to obtain the supported high-entropy Pt catalyst.

[0010] Optionally, the metal precursor salt is one or more of nitrates, chlorides, and acetates.

[0011] Optionally, in the catalyst, the atomic percentage of Pt is 5-30%, the atomic percentage of Zn is 10-30%, the atomic percentage of Mn is 10-30%, and the atomic percentage of A is 15-65%.

[0012] Optionally, the selected solvent may include one or more of water, methanol, and ethanol.

[0013] Optionally, the support includes one or more of nitrides, oxides, and carbides; the nitride is one or more of boron nitride and silicon nitride; the oxide is one or more of silicon oxide, aluminum oxide, and cerium oxide; and the carbide is silicon carbide.

[0014] Optionally, the carrier undergoes a drying pretreatment at a temperature of 100-180°C, preferably for a time of 1-12 hours.

[0015] Optionally, the impregnation treatment is a co-impregnation treatment.

[0016] Optionally, the concentration of the metal precursor salt solution is determined according to the metal content in the catalyst, and the volume of the precursor solution is greater than or equal to the total pore volume of the porous support. That is, the impregnation method includes equal-volume impregnation and excessive impregnation. The equal-volume impregnation is when the volume of the metal salt mixture solution is close to that of the support pores, and after impregnation, it is left to stand at room temperature to promote diffusion into the pores. The excessive impregnation is when the volume of the impregnation liquid is greater than that of the support, and stirring is required. The stirring and impregnation treatment time is 0.5-12 hours.

[0017] The concentration of the metal precursor salt solution is 0.003-0.3 mol / L.

[0018] Optionally, the drying temperature in step S3 is 40-120℃, and the drying time is 2-24h.

[0019] Optionally, the roasting atmosphere is air, nitrogen or argon, the roasting temperature is 300-700℃, the roasting time is 2-6h, and more preferably the heating rate is 5-20℃ / min.

[0020] Optionally, in the reduction process, the reducing atmosphere is hydrogen, carbon monoxide, or nitrogen. Preferably, the reducing atmosphere is hydrogen and carbon monoxide, wherein the volume concentration of hydrogen is 5-100%; the reduction temperature is 400-800°C, the reduction time is 1-6 h, and more preferably the heating rate is 5-20°C / min.

[0021] The second aspect of the present invention provides the application of a supported high-entropy Pt-based catalyst obtained by any preparation method of the first aspect in the dehydrogenation of propane to propylene.

[0022] Optionally, the reaction temperature is 550-600℃.

[0023] Optionally, the process is carried out in an atmospheric pressure fixed-bed reactor, in which propane or a propane-containing mixture is introduced into the reactor, the mixture further comprising hydrogen and / or diluent nitrogen. When the mixture includes hydrogen, the volume ratio of propane to hydrogen is 1:0.2-1:2.

[0024] The preparation method and application of the supported metal catalyst provided by this invention have at least the following advantages:

[0025] This invention loads Pt, Zn, Mn, and at least two non-noble metal elements onto a support to achieve the nano-sizing of high-entropy materials. This significantly increases the exposure of the active phase and suppresses side reactions such as cracking, hydrogenolysis, and carbon deposition, making it suitable for catalysis. Specifically, it improves the dispersion of high-entropy metal particles, thereby increasing the utilization rate of noble metals; enhances the thermal stability of nano-metal particles at high temperatures; strengthens the catalytic activity and stability of metal catalysts; exhibits unique stability, especially in high-temperature reactions; and is applicable to a wide range of metal elements and metal precursors. Compared with general non-high-entropy catalysts, the high-entropy catalyst prepared by this method exhibits higher conversion rate, higher selectivity, and catalytic stability in propane dehydrogenation. Using a high-entropy catalyst to stabilize Pt species offers advantages over current methods such as molecular sieve encapsulation and defect anchoring of Pt species on supports, including simpler preparation processes and lower costs.

[0026] Compared with general high-entropy material preparation methods, including precipitation, mechanochemical, and hydrothermal methods, the high-entropy material preparation process provided by this invention is simpler; and this invention can obtain nanoscale high-entropy materials, which, compared with traditional unsupported high-entropy materials, can improve the utilization rate of metal atoms and reduce raw material costs in catalytic applications. Attached Figure Description

[0027] Figure 1 The XRD diffraction pattern of the A1 catalyst obtained in Example 1 is shown below.

[0028] Figure 2 The XRD diffraction pattern of the A2 catalyst obtained in Example 2 is shown below.

[0029] Figure 3 This is a high-angle annular dark-field scanning transmission electron microscope image of the A2 catalyst obtained in Example 2;

[0030] Figure 4 The linear scan spectrum of the A2 catalyst obtained in Example 2;

[0031] Figure 5 The catalyst activity diagram is shown for the A1 catalyst obtained in Example 2;

[0032] Figure 6 The catalytic activity diagram of the A2 catalyst obtained in Example 2 at 600°C is shown.

[0033] Figure 7 This is a STEM image of the A2 catalyst obtained in Example 2 after reaction at 600°C;

[0034] Figure 8 The catalytic activity diagram of the A2 catalyst obtained in Example 2 at 550°C is shown.

[0035] Figure 9 This is a long-term stability graph of the A2 catalyst obtained in Example 2 under the same gas ratio in industrial applications;

[0036] Figure 10 The activity diagram of the C1 catalyst obtained in Comparative Example 1 is shown.

[0037] Figure 11 This is a STEM image of the comparative C2 catalyst;

[0038] Figure 12 This is a STEM image of the comparative C2 catalyst after reaction at 600℃ for 24 h;

[0039] Figure 13 The catalytic activity diagram of C4 obtained in Comparative Example 4 is shown.

[0040] Figure 14 The activity diagram of the C6 catalyst obtained in Comparative Example 6 is shown.

[0041] Figure 15 The activity diagram of the C7 catalyst obtained in Comparative Example 7 is shown.

[0042] Figure 16 The image shows the activity of the C8 catalyst obtained in Comparative Example 8. Detailed Implementation

[0043] The present invention will be further described clearly and completely below through embodiments, but is not limited to the examples described herein. The examples are only a part of the present invention, and not all of the embodiments.

[0044] Example 1

[0045] The supported high-entropy Pt-based catalyst obtained in this embodiment has a metal phase composition of Mn. 0.2 Co 0.2 Zn 0.2 Cu 0.2 Pt 0.2 The metal precursor salts were (CH3COO2)Mn·4H2O, Co(NO3)2·6H2O, Zn(NO3)2·6H2O, Cu(NO3)2·3H2O, and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 1.0%, and the atomic ratio of Mn, Co, Zn, Cu, and Pt was 0.2:0.2:0.2:0.2:0.2. The support used was SiO2 aerogel.

[0046] Prepare 0.3 mol / L aqueous solutions of metal salts separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 750 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions. Dry the silica support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal precursor salt solution, and let it stand at room temperature for 2 h. The impregnated sample is subjected to solvent evaporation and drying treatment at 50℃ for 12 h to obtain the first product.

[0047] The first product was calcined at 500°C for 4 hours in air at a heating rate of 5°C / min to obtain a highly dispersed high-entropy metal oxide on a silica support. Next, the supported high-entropy oxide was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, and then treated with 20% H2 / Ar for 2 hours to obtain a highly dispersed and stable high-entropy Pt-based catalyst, named Al.

[0048] The crystal form of the samples obtained in the examples was analyzed by XRD, such as... Figure 1 As shown, sample A1 exhibits a face-centered cubic phase structure that is different from that of each metal.

[0049] Example 2

[0050] The supported high-entropy Pt-based catalyst obtained in this embodiment has a metal phase composition of Mn. 0.2 Co 0.2 Zn 0.2 Cu 0.2 Pt 0.2The metal precursors were (CH3COO2)Mn·4H2O, Co(NO3)2·6H2O, Zn(NO3)2·6H2O, Cu(NO3)2·3H2O, and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 0.5%, and the atomic ratio of Mn, Co, Zn, Cu, and Pt was 0.2:0.2:0.2:0.2:0.2. The support used was SiO2 aerogel.

[0051] Prepare 0.3 mol / L aqueous solutions of metal salts separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 750 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions. Dry the silica support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal salt solution, and let it stand at room temperature for 2 h. Perform solvent evaporation and drying treatment on the impregnated sample at 50℃ for 12 h to obtain the first product.

[0052] The first product was calcined at 500°C for 4 hours in air at a heating rate of 5°C / min to obtain a highly dispersed high-entropy metal oxide on a silica support. Next, the supported high-entropy oxide was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, and then treated with 20% H2 / Ar for 2 hours to obtain a highly dispersed and stable high-entropy Pt-based catalyst, named A2.

[0053] The samples obtained in Example 2 were analyzed by XRD and high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM), such as... Figure 2 The absence of obvious diffraction peaks in the XRD pattern indicates the absence of large metal species or a loading below the detection limit. Figure 3 It can be seen that the catalyst particles are uniformly distributed, with no large particle aggregation. Particle size distribution data obtained through particle size analysis shows that the catalyst particles are mainly concentrated at 1.5 nm. Linear scanning results indicate the presence of five elements (e.g., ...) on the surface metal particles. Figure 4 ).

[0054] Example 3

[0055] The supported high-entropy Pt-based catalyst obtained in this embodiment has a metal phase composition of Mn. 0.2 Co 0.2 Zn 0.2 Cu 0.2 Pt 0.2The metal precursors were (CH3COO2)Mn·4H2O, Co(NO3)2·6H2O, Zn(NO3)2·6H2O, Cu(NO3)2·3H2O, and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 0.3%, and the atomic ratio of Mn, Co, Zn, Cu, and Pt was 0.2:0.2:0.2:0.2:0.2. The support used was SiO2 aerogel.

[0056] Prepare 0.3 mol / L aqueous solutions of metal salts separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 750 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions. Dry the silica support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal precursor salt solution, and let it stand at room temperature for 2 h. The impregnated sample is subjected to solvent evaporation and drying treatment at 50℃ for 12 h to obtain the first product.

[0057] The first product was calcined at 500°C for 4 hours in air at a heating rate of 5°C / min to obtain a highly dispersed high-entropy metal oxide on a silica support. Next, the supported high-entropy oxide was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, followed by treatment with 20% H2 / Ar for 2 hours to obtain a highly dispersed and stable high-entropy Pt-based catalyst, named A3.

[0058] Example 4

[0059] The supported high-entropy Pt-based catalyst obtained in this embodiment has a metal phase composition of Mn. 0.25 Co 0.15 Zn 0.2 Cu 0.2 Pt 0.2 The metal precursors were (CH3COO2)Mn·4H2O, Co(NO3)2·6H2O, Zn(NO3)2·6H2O, Cu(NO3)2·3H2O, and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 0.5%, and the atomic ratio of Mn, Co, Zn, Cu, and Pt was 0.25:0.15:0.2:0.2:0.2. The support used was SiO2 aerogel.

[0060] Prepare 0.3 mol / L aqueous solutions of metal salts separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 750 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions. Dry the silica support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal precursor salt solution, and let it stand at room temperature for 2 h. The impregnated sample is subjected to solvent evaporation and drying treatment at 50℃ for 12 h to obtain the first product.

[0061] The first product was calcined at 500°C for 4 h in air at a heating rate of 5°C / min to obtain a highly dispersed high-entropy metal oxide on a silica support. Next, the supported high-entropy oxide was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, and then treated with 20% H2 / Ar for 2 h to obtain a highly dispersed and stable high-entropy Pt-based catalyst, named A4.

[0062] Example 5

[0063] The supported high-entropy Pt-based catalyst obtained in this embodiment has a metal phase composition of Mn. 0.2 Co 0.15 Zn 0.25 Cu 0.2 Pt 0.2 The metal precursors were (CH3COO2)Mn·4H2O, Co(NO3)2·6H2O, Zn(NO3)2·6H2O, Cu(NO3)2·3H2O, and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 0.5%, and the atomic ratio of Mn, Co, Zn, Cu, and Pt was 0.2:0.15:0.25:0.2:0.2. The support used was SiO2 aerogel.

[0064] Prepare 0.3 mol / L aqueous solutions of metal salts separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 750 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions. Dry the silica support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal precursor salt solution, and let it stand at room temperature for 2 h. The impregnated sample is subjected to solvent evaporation and drying treatment at 50℃ for 12 h to obtain the first product.

[0065] The first product was calcined at 500°C for 4 hours in air at a heating rate of 5°C / min to obtain a highly dispersed high-entropy metal oxide on a silica support. Next, the supported high-entropy oxide was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, and then treated with 20% H2 / Ar for 2 hours to obtain a highly dispersed and stable high-entropy Pt-based catalyst, named A5.

[0066] Example 6

[0067] The supported high-entropy Pt-based catalyst obtained in this embodiment has a metal phase composition of Mn. 0.2 Co 0.15 Zn 0.2 Cu 0.25 Pt 0.2 The metal precursors were (CH3COO2)Mn·4H2O, Co(NO3)2·6H2O, Zn(NO3)2·6H2O, Cu(NO3)2·3H2O, and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 0.5%, and the atomic ratio of Mn, Co, Zn, Cu, and Pt was 0.2:0.15:0.2:0.25:0.2. The support used was SiO2 aerogel.

[0068] Prepare 0.3 mol / L aqueous solutions of metal salts separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 750 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions. Dry the silica support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal precursor salt solution, and let it stand at room temperature for 2 h. The impregnated sample is subjected to solvent evaporation and drying treatment at 50℃ for 12 h to obtain the first product.

[0069] The first product was calcined at 500°C for 4 hours in air at a heating rate of 5°C / min to obtain a highly dispersed high-entropy metal oxide on a silica support. Next, the supported high-entropy oxide was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, followed by treatment with 20% H2 / Ar for 2 hours to obtain a highly dispersed and stable high-entropy Pt-based catalyst, named A6.

[0070] Example 7

[0071] The supported high-entropy Pt-based catalyst obtained in this embodiment has a metal phase composition of Mn. 0.2 Co 0.15 Zn 0.2 Cu 0.2 Pt 0.25The metal precursors were (CH3COO2)Mn·4H2O, Ni(NO3)2·6H2O, Co(NO3)2·6H2O, Zn(NO3)2·6H2O, Cu(NO3)2·3H2O, and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 0.5%, and the atomic ratio of Mn, Ni, Co, Zn, Cu, and Pt was 0.2:0.1:1:0.2:0.2:0.2. The support used was SiO2 aerogel.

[0072] Prepare 0.3 mol / L aqueous solutions of metal salts separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 750 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions. Dry the silica support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal precursor salt solution, and let it stand at room temperature for 2 h. The impregnated sample is subjected to solvent evaporation and drying treatment at 50℃ for 12 h to obtain the first product.

[0073] The first product was calcined at 500°C for 4 hours in air at a heating rate of 5°C / min to obtain a highly dispersed high-entropy metal oxide on a silica support. Next, the supported high-entropy oxide was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, and then treated with 20% H2 / Ar for 2 hours to obtain a highly dispersed and stable high-entropy Pt-based catalyst, named A7.

[0074] Example 8

[0075] The supported high-entropy Pt-based catalyst obtained in this embodiment has a metal phase composition of Mn. 0.25 Co 0.15 Zn 0.15 Cu 0.15 Pt 0.3 The metal precursors were (CH3COO2)Mn·4H2O, Co(NO3)2·6H2O, Zn(NO3)2·6H2O, Cu(NO3)2·3H2O, and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 0.5%, and the atomic ratio of Mn, Co, Zn, Cu, and Pt was 0.25:0.15:0.15:0.15:0.3. The support used was SiO2 aerogel.

[0076] Prepare 0.3 mol / L aqueous solutions of metal salts separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 750 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions. Dry the silica support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal precursor salt solution, and let it stand at room temperature for 2 h. The impregnated sample is subjected to solvent evaporation and drying treatment at 50℃ for 12 h to obtain the first product.

[0077] The first product was calcined at 500°C for 4 hours in air at a heating rate of 5°C / min to obtain a highly dispersed high-entropy metal oxide on a silica support. Next, the supported high-entropy oxide was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, and then treated with 20% H2 / Ar for 2 hours to obtain a highly dispersed and stable high-entropy Pt-based catalyst, named A8.

[0078] Example 9

[0079] The supported high-entropy Pt-based catalyst obtained in this embodiment has a metal phase composition of Mn. 0.15 Co 0.15 Zn 0.15 Cu 0.25 Pt 0.3 The metal precursors were (CH3COO2)Mn·4H2O, Co(NO3)2·6H2O, Zn(NO3)2·6H2O, Cu(NO3)2·3H2O, and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 0.5%, and the atomic ratio of Mn, Co, Zn, Cu, and Pt was 0.15:0.15:0.15:0.25:0.3. The support used was SiO2 aerogel.

[0080] Prepare 0.3 mol / L aqueous solutions of metal salts separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 750 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions for later use. Dry the silica support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal precursor salt solution, and let it stand at room temperature for 2 h. Perform solvent evaporation and drying treatment on the impregnated sample at 50℃ for 12 h to obtain the first product.

[0081] The first product was calcined at 500°C for 4 hours in air at a heating rate of 5°C / min to obtain a highly dispersed high-entropy metal oxide on a silica support. Next, the supported high-entropy oxide was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, and then treated with 20% H2 / Ar for 2 hours to obtain a highly dispersed and stable high-entropy Pt-based catalyst, named A9.

[0082] Example 10

[0083] The supported high-entropy Pt-based catalyst obtained in this embodiment has a metal phase composition of Mn. 0.3 Co 0.15 Zn 0.15 Cu 0.15 Pt 0.25 The metal precursors were (CH3COO2)Mn·4H2O, Co(NO3)2·6H2O, Zn(NO3)2·6H2O, Cu(NO3)2·3H2O, and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 0.5%, and the atomic ratio of Mn, Co, Zn, Cu, and Pt was 0.3:0.15:0.15:0.15:0.25. The support used was SiO2 aerogel.

[0084] Prepare 0.3 mol / L aqueous solutions of metal salts separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 750 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions. Dry the silica support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal precursor salt solution, and let it stand at room temperature for 2 h. The impregnated sample is subjected to solvent evaporation and drying treatment at 50℃ for 12 h to obtain the first product.

[0085] The first product was calcined at 500°C for 4 hours in air at a heating rate of 5°C / min to obtain a highly dispersed high-entropy metal oxide on a silica support. Next, the supported high-entropy oxide was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, and then treated with 20% H2 / Ar for 2 hours to obtain a highly dispersed and stable high-entropy Pt-based catalyst, named A10.

[0086] Example 11

[0087] The supported high-entropy Pt-based catalyst obtained in this embodiment has a metal phase composition of Mn. 0.15 Co 0.15 Zn 0.25 Cu 0.15 Pt 0.3The metal precursors were (CH3COO2)Mn·4H2O, Co(NO3)2·6H2O, Zn(NO3)2·6H2O, Cu(NO3)2·3H2O, and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 0.5%, and the atomic ratio of Mn, Co, Zn, Cu, and Pt was 0.15:0.15:0.25:0.15:0.3. The support used was SiO2 aerogel.

[0088] Prepare 0.3 mol / L aqueous solutions of metal salts separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 750 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions. Dry the silica support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal precursor salt solution, and let it stand at room temperature for 2 h. The impregnated sample is subjected to solvent evaporation and drying treatment at 50℃ for 12 h to obtain the first product.

[0089] The first product was calcined at 500°C for 4 h in air at a heating rate of 5°C / min to obtain a highly dispersed high-entropy metal oxide on a silica support. Next, the supported high-entropy oxide was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, followed by treatment with 20% H2 / Ar for 2 h to obtain a highly dispersed and stable high-entropy Pt-based catalyst, named Al1.

[0090] Example 12

[0091] The supported high-entropy Pt-based catalyst obtained in this embodiment has a metal phase composition of Mn. 0.2 Co 0.2 Zn 0.2 Cu 0.2 Pt 0.2 The metal precursors were (CH3COO2)Mn·4H2O, Co(NO3)2·6H2O, Zn(NO3)2·6H2O, Cu(NO3)2·3H2O, and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 0.5%, and the atomic ratio of Mn, Co, Zn, Cu, and Pt was 0.2:0.2:0.2:0.2:0.2. The support used was SiC.

[0092] Prepare 0.3 mol / L aqueous solutions of metal salts separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 225 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions. Dry the support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal precursor salt solution, and let it stand at room temperature for 2 h. The impregnated sample is subjected to solvent evaporation and drying treatment at 50℃ for 12 h to obtain the first product.

[0093] The first product was calcined at 500°C for 4 hours in air at a heating rate of 5°C / min to obtain a highly dispersed high-entropy metal oxide on a silica support. Next, the supported high-entropy oxide was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, and then treated with 20% H2 / Ar for 2 hours to obtain a highly dispersed and stable high-entropy Pt-based catalyst, named Al2.

[0094] Example 13

[0095] The supported high-entropy Pt-based catalyst obtained in this embodiment has a metal phase composition of Mn. 0.2 Co 0.2 Zn 0.2 Cu 0.2 Pt 0.2 The metal precursors were (CH3COO2)Mn·4H2O, Co(NO3)2·6H2O, Zn(NO3)2·6H2O, Cu(NO3)2·3H2O, and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 0.5%, and the atomic ratio of Mn, Co, Zn, Cu, and Pt was 0.2:0.2:0.2:0.2:0.2. The support used was TiO2.

[0096] Prepare 0.3 mol / L aqueous solutions of metal salts separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 225 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions. Dry the support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal salt solution, and let it stand at room temperature for 2 h. The impregnated sample is subjected to solvent evaporation and drying treatment at 50℃ for 12 h to obtain the first product.

[0097] The first product was calcined at 500°C for 4 hours in air at a heating rate of 5°C / min to obtain a highly dispersed high-entropy metal oxide on a silica support. Next, the supported high-entropy oxide was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, followed by treatment with 20% H2 / Ar for 2 hours to obtain a highly dispersed and stable high-entropy Pt-based catalyst, named A13.

[0098] Example 14

[0099] The supported high-entropy Pt-based catalyst obtained in this embodiment has a metal phase composition of Mn. 0.2 Co 0.2 Zn 0.2 Cu 0.2 Pt 0.2 The metal precursors were (CH3COO2)Mn·4H2O, Co(NO3)2·6H2O, Zn(NO3)2·6H2O, Cu(NO3)2·3H2O, and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 0.5%, and the atomic ratio of Mn, Co, Zn, Cu, and Pt was 0.2:0.2:0.2:0.2:0.2. The support used was Al2O3.

[0100] Prepare 0.3 mol / L aqueous solutions of metal salts separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 600 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions. Dry the support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal precursor salt solution, and let it stand at room temperature for 2 h. The impregnated sample is subjected to solvent evaporation and drying treatment at 50℃ for 12 h to obtain the first product.

[0101] The first product was calcined at 500°C for 4 hours in air at a heating rate of 5°C / min to obtain a highly dispersed high-entropy metal oxide on a silica support. Next, the supported high-entropy oxide was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, followed by treatment with 20% H2 / Ar for 2 hours to obtain a highly dispersed and stable high-entropy Pt-based catalyst, named A14.

[0102] Comparative Example 1

[0103] The catalyst metal phase composition obtained in this comparative example is Pt, and the metal precursor is H2PtCl6. Based on the support, the mass ratio of metal Pt to support is 0.5%. The support used is SiO2 aerogel.

[0104] Prepare a 0.3 mol / L H₂PtCl₆ aqueous solution. Take the H₂PtCl₆ aqueous solution according to the above mass ratio, dilute with deionized water to 600 μL, and ultrasonically mix thoroughly. Set aside. Weigh 750 mg of dried carrier into a vial, and uniformly impregnate the carrier with the H₂PtCl₆ solution using the equal-volume impregnation method. Let stand at room temperature for 2 h. Perform solvent evaporation and drying treatment on the impregnated sample at 50 °C for 12 h to obtain the first product.

[0105] The first product was calcined at 500°C for 4 hours in air at a heating rate of 5°C / min to obtain platinum oxide highly dispersed on a silica support. Next, the catalyst was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, and then treated with 20% H2 / Ar for 2 hours to obtain the catalyst, named C1.

[0106] Comparative Example 2

[0107] The catalyst metal phase composition obtained in this comparative example is Mn 0.4 Zn 0.4 Pt 0.2 The metal precursors were (CH3COO2)Mn·4H2O, Zn(NO3)2·6H2O, and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 0.5%, and the atomic ratio of Mn, Zn, and Pt was 0.4:0.4:0.2. The support used was SiO2 aerogel.

[0108] Prepare 0.3 mol / L aqueous solutions of metal salts separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 600 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions. Dry the silica support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal precursor salt solution, and let it stand at room temperature for 2 h. The impregnated sample is subjected to solvent evaporation and drying treatment at 50℃ for 12 h to obtain the first product.

[0109] The first product was calcined at 500°C for 4 hours in air at a heating rate of 5°C / min to obtain a metal oxide highly dispersed on a silica support. Next, the supported catalyst was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, and then treated with 20% H2 / Ar for 2 hours. The resulting catalyst was named C2.

[0110] Comparative Example 3

[0111] The catalyst metal phase composition obtained in this comparative example is Mn 0.267 Zn 0.267 Cu 0.267 Pt 0.2The metal precursors were (CH3COO2)Mn·4H2O, Zn(NO3)2·6H2O, Cu(NO3)2·3H2O, and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 0.5%, and the atomic ratio of Mn, Zn, Cu, and Pt was 0.267:0.267:0.267:0.2. The support used was SiO2 aerogel.

[0112] Prepare 0.3 mol / L metal salt solutions separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 600 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions. Dry the silica support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal precursor salt solution, and let it stand at room temperature for 2 h. The impregnated sample is subjected to solvent evaporation and drying treatment at 50℃ for 12 h to obtain the first product.

[0113] The first product was calcined at 500°C for 4 hours in air at a heating rate of 5°C / min to obtain a metal oxide highly dispersed on a silica support. Next, the supported oxide was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, and then treated with 20% H2 / Ar for 2 hours. The resulting catalyst was named C3.

[0114] Comparative Example 4

[0115] The catalyst metal phase composition obtained in this comparative example is Co. 0.8 Pt 0.2 The metal precursors were Co(NO3)2·6H2O and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 0.5%, and the atomic ratio of Co to Pt was 0.8:0.2. The support used was SiO2 aerogel.

[0116] Prepare 0.3 mol / L aqueous solutions of metal salts separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 600 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions. Dry the silica support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal precursor salt solution, and let it stand at room temperature for 2 h. The impregnated sample is subjected to solvent evaporation and drying treatment at 50℃ for 12 h to obtain the first product.

[0117] The first product was calcined at 500°C for 4 hours in air at a heating rate of 5°C / min to obtain a metal oxide highly dispersed on a silica support. Next, the supported oxide was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, and then treated with 20% H2 / Ar for 2 hours. The resulting catalyst was named C4.

[0118] Comparative Example 5

[0119] The catalyst metal phase composition obtained in this comparative example is Cu. 0.8 Pt 0.2 The metal precursors were Cu(NO3)2·3H2O and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 0.5%, and the atomic ratio of Cu to Pt was 0.8:0.2. The support used was SiO2 aerogel.

[0120] Prepare 0.3 mol / L aqueous solutions of metal salts separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 600 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions. Dry the silica support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal precursor salt solution, and let it stand at room temperature for 2 h. The impregnated sample is subjected to solvent evaporation and drying treatment at 50℃ for 12 h to obtain the first product.

[0121] The first product was calcined at 500°C for 4 hours in air at a heating rate of 5°C / min to obtain a metal oxide highly dispersed on a silica support. Next, the supported oxide was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, and then treated with 20% H2 / Ar for 2 hours. The resulting catalyst was named C5.

[0122] Comparative Example 6

[0123] The catalyst metal phase composition obtained in this comparative example is Zn. 0.5 Pt 0.5 The metal precursors were Zn(NO3)2·6H2O and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 0.5%, and the atomic ratio of Zn to Pt was 0.5:0.5. The support used was SiO2 aerogel.

[0124] Prepare 0.3 mol / L aqueous solutions of metal salts separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 600 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions. Dry the silica support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal precursor salt solution, and let it stand at room temperature for 2 h. The impregnated sample is subjected to solvent evaporation and drying treatment at 50℃ for 12 h to obtain the first product.

[0125] The first product was calcined at 500°C for 4 hours in air at a heating rate of 5°C / min to obtain a metal oxide highly dispersed on a silica support. Next, the supported oxide was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, and then treated with 20% H2 / Ar for 2 hours. The resulting catalyst was named C6.

[0126] Comparative Example 7

[0127] The catalyst metal phase composition obtained in this comparative example is Sn. 0.8 Pt 0.5 The metal precursors were SnCl2·2H2O and H2PtCl6. Using the support as a reference, the mass ratio of metal Pt to support was 0.5%, and the atomic ratio of Sn to Pt was 1:0.5. Al2O3 was used as the support. 0.3 mol / L aqueous solutions of the metal salts were prepared. Each metal salt solution was taken according to the above mass ratio and diluted with deionized water to 600 μL. The solutions were ultrasonically mixed to obtain the metal precursor salt solutions. The Al2O3 support was dried at 120℃ for 2 h to obtain the dried support. 750 mg of the dried support was weighed into a vial, and the metal precursor salt solution was uniformly impregnated onto the support using an equal-volume impregnation method and allowed to stand at room temperature for 2 h. The impregnated sample was subjected to solvent evaporation and drying treatment at 50℃ for 12 h to obtain the first product.

[0128] The first product was calcined in air at 500°C for 4 h at a heating rate of 5°C / min to obtain a catalyst precursor. The catalyst precursor was then heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, followed by treatment with 20% H2 / Ar for 2 h. The resulting catalyst was named C7.

[0129] Comparative Example 8

[0130] The catalyst metal phase composition obtained in this comparative example is Mn 0.2 Ni 0.2 Cu 0.2 :Co 0.2 Pt 0.2The metal precursors were (CH3COO2)Mn·4H2O, Ni(NO3)2·6H2O, Cu(NO3)2·3H2O, Co(NO3)2·6H2O, and H2PtCl6. Based on the support, the mass ratio of metal Pt to support was 0.5%, and the atomic ratio of Mn, Ni, Cu, Co, and Pt was 0.2:0.2:0.2:0.2:0.2. The support used was SiO2.

[0131] Prepare 0.3 mol / L metal salt solutions separately. Take each metal salt solution according to the above mass ratio, dilute with deionized water to 600 μL, and ultrasonically mix thoroughly to obtain metal precursor salt solutions. Dry the silica support at 120℃ for 2 h to obtain a dried support for later use. Weigh 750 mg of the dried support into a small bottle, and use the equal-volume impregnation method to uniformly impregnate the support with the metal precursor salt solution, and let it stand at room temperature for 2 h. The impregnated sample is subjected to solvent evaporation and drying treatment at 50℃ for 12 h to obtain the first product.

[0132] The first product was calcined at 500°C for 4 hours in air at a heating rate of 5°C / min to obtain a metal oxide highly dispersed on a silica support. Next, the supported oxide was heated to 600°C in N2 atmosphere at a heating rate of 5°C / min, and then treated with 20% H2 / Ar for 2 hours. The resulting catalyst was named C8.

[0133] The specific calculation methods for the Pt loading and the amounts of each metal in the catalyst obtained in the above embodiments and comparative examples are as follows: The loading is a theoretically calculated value. According to the target loading, the solutions of each metal precursor are measured. The Pt loading is the mass ratio of Pt to SiO2 or Al2O3. Based on this, the amount of each metal element added is determined according to the molar ratio of Pt to each metal element. Some parameters of each embodiment and comparative example are shown in Table 1.

[0134] Table 1. Parameters for each embodiment and comparative example.

[0135]

[0136] The following test examples 1-10 illustrate the propane dehydrogenation to propylene production using the catalysts described in the above examples.

[0137] The reaction test uses a fixed-bed reactor, equipped with an open-tube resistance furnace and an intelligent temperature controller to provide heat for the reaction and to detect and control the temperature; a seven-star flow meter controller controls the flow rate.

[0138] The alkane and olefin contents in the product were analyzed online using a GC7900 gas chromatograph, and the reaction conversion rate and product selectivity were calculated. The product selectivity was calculated using the area normalization method.

[0139] Test Example 1

[0140] The propane dehydrogenation performance of the A1 catalyst obtained in Example 1 was determined in a continuous fixed-bed microreactor. Specific conditions were as follows: catalyst dosage 0.1 g, reaction temperature 600 °C, reaction pressure atmospheric pressure, total reaction gas flow rate 30 ml / min, of which propane flow rate was 3 ml / min, H2 flow rate was 3 ml / min, and the remainder was N2 flow rate. The initial propane conversion rate of the obtained A1 catalyst was 54.5%, and the propylene selectivity was 95%. After 480 min of reaction, the propane conversion rate was 51.32%, and the propylene selectivity stabilized at 95% (e.g., ...). Figure 5 (as shown in Table 2).

[0141] Test Example 2

[0142] The propane dehydrogenation performance of the A2 catalyst obtained in Example 2 was determined in a continuous fixed-bed microreactor. Specific conditions were as follows: catalyst dosage 0.1 g, reaction temperature 600 °C, reaction pressure atmospheric pressure, total reaction gas flow rate 30 ml / min (propane 3 ml / min, H2 3 ml / min, remainder N2). The resulting A1 catalyst initially showed a propane conversion of 56.7% and a propylene selectivity of 94.2%. After 24 h of reaction, the propane conversion was 51.3%, the propylene selectivity stabilized at 94.5%, and the deactivation rate constant was only 0.009 h⁻¹. -1 (like Figure 6 (as shown in Table 2).

[0143] High-angle annular dark-field scanning electron microscopy (HAADF-STEM) was used to analyze the samples obtained after the reaction in test side 2. The results are as follows: Figure 7 As shown, the catalyst particles remain uniformly distributed, with no large particle aggregation. A particle size distribution diagram obtained through particle size analysis shows that the catalyst particles are mainly concentrated at 1.4 nm (e.g., ...). Figure 7 ).

[0144] Test Example 3

[0145] The propane dehydrogenation performance of the A2 catalyst obtained in Example 2 was determined in a continuous fixed-bed microreactor. Specific conditions were as follows: catalyst dosage 0.1 g, reaction temperature 550 °C, reaction pressure atmospheric pressure, total reaction gas flow rate 30 ml / min (propane 3 ml / min, H2 3 ml / min, remainder N2). The initial propane conversion rate of the A2 catalyst was 36.4%, and the propylene selectivity was 96.7%. After 24 h of reaction, the propane conversion rate was 34.7%, the propylene selectivity stabilized at 98.4%, and the deactivation rate was only 0.003 h. -1 (like Figure 8 (As shown).

[0146] Test Example 4

[0147] The propane dehydrogenation performance of the A2 catalyst obtained in Example 2 was determined in a continuous fixed-bed microreactor. Specific conditions were as follows: catalyst dosage 0.1 g, reaction temperature 550 °C, reaction pressure atmospheric pressure, total reaction gas flow rate 4.8 ml / min (propane flow rate 3 ml / min, H2 flow rate 1.8 ml / min), and no nitrogen dilution gas was added. The initial propane conversion rate of the A2 catalyst was 19.6%, and the propylene selectivity was 88.6%. After 200 h of reaction, the propane conversion rate was 18.1%, the propylene selectivity stabilized at 93.2%, and the deactivation rate was only 0.0004 h. -1 (like Figure 9 (As shown).

[0148] Test Example 5

[0149] The propane dehydrogenation performance of the A3 catalyst obtained in Example 3 was determined in a continuous fixed-bed microreactor. Specific conditions were as follows: catalyst dosage 0.1 g, reaction temperature 600 °C, reaction pressure atmospheric pressure, total reaction gas flow rate 30 ml / min, including 3 ml / min propane, 3 ml / min H2, and 24 ml / min N2. The initial propane conversion of the A3 catalyst was 61%, and the propylene selectivity was 91.8%.

[0150] Test Example 6

[0151] The propane dehydrogenation performance of the A4 catalyst obtained in Example 4 was determined in a continuous fixed-bed microreactor. Specific conditions were as follows: catalyst dosage 0.1 g, reaction temperature 600 °C, reaction pressure atmospheric pressure, total reaction gas flow rate 30 ml / min, including 3 ml / min propane, 3 ml / min H2, and 24 ml / min N2. The initial propane conversion of the A4 catalyst was 58%, and the propylene selectivity was 96%.

[0152] Test Example 7

[0153] The propane dehydrogenation performance of the A5 catalyst obtained in Example 5 was determined in a continuous fixed-bed microreactor. Specific conditions were as follows: catalyst dosage 0.1 g, reaction temperature 600 °C, reaction pressure atmospheric pressure, total reaction gas flow rate 30 ml / min, including 3 ml / min propane, 3 ml / min H2, and 24 ml / min N2. The initial propane conversion of the A5 catalyst was 57%, and the propylene selectivity was 96.5%.

[0154] Test Example 8

[0155] The propane dehydrogenation performance of the A7 catalyst obtained in Example 7 was determined in a continuous fixed-bed microreactor. Specific conditions were as follows: catalyst dosage 0.1 g, reaction temperature 600 °C, reaction pressure atmospheric pressure, total reaction gas flow rate 60 ml / min, including 6 ml / min propane, 6 ml / min H2, and 48 ml / min N2. The initial propane conversion rate of the A7 catalyst was 50.5%, and the propylene selectivity was 94%. After 8 hours of reaction, the propane conversion rate was 40.5%, and the propylene selectivity stabilized at 96%.

[0156] Test Example 9

[0157] The propane dehydrogenation performance of the A8 catalyst obtained in Example 8 was determined in a continuous fixed-bed microreactor. Specific conditions were as follows: catalyst dosage 0.1 g, reaction temperature 600 °C, reaction pressure atmospheric pressure, total reaction gas flow rate 30 ml / min, of which propane flow rate was 3 ml / min, H2 flow rate was 3 ml / min, and N2 flow rate was 24 ml / min. The initial propane conversion rate of the A8 catalyst was 52.5%, and the propylene selectivity was 95.2% (Table 2).

[0158] Test Case 10

[0159] The propane dehydrogenation performance of the A9 catalyst obtained in Example 9 was determined in a continuous fixed-bed microreactor. Specific conditions were as follows: catalyst dosage 0.1 g, reaction temperature 600 °C, reaction pressure atmospheric pressure, total reaction gas flow rate 30 ml / min, including 3 ml / min propane, 3 ml / min H2, and 24 ml / min N2. The initial propane conversion of the A9 catalyst was 53.8%, and the propylene selectivity was 94.5% (Table 2).

[0160] The following test examples 11-18 illustrate the production of propylene from propane via dehydrogenation using the catalysts in the comparative examples described above.

[0161] Test Example 11

[0162] The propane dehydrogenation performance of the C1 catalyst obtained in Comparative Example 1 was determined in a continuous fixed-bed microreactor. Specific conditions were as follows: catalyst dosage 0.1 g, reaction temperature 600 °C, reaction pressure atmospheric pressure, total reaction gas flow rate 30 mL / min (propane 3 mL / min, H2 3 mL / min, nitrogen 24 mL / min). The initial propane conversion of the C1 catalyst was 47%, and the propylene selectivity was 77.4%. After 420 min of reaction, the propane conversion was 23.5%, the propylene selectivity was 84.5%, and the deactivation rate constant was 0.15 h⁻¹. -1 (like Figure 10 (As shown).

[0163] Test Example 12

[0164] The propane dehydrogenation performance of the C2 catalyst obtained in Comparative Example 2 was determined in a continuous fixed-bed microreactor. Specific conditions were as follows: catalyst dosage 0.1 g, reaction temperature 600 °C, reaction pressure atmospheric pressure, total reaction gas flow rate 30 mL / min (propane 3 mL / min, H2 3 mL / min, nitrogen 24 mL / min). The initial propane conversion of the C2 catalyst was 55.7%, and the propylene selectivity was 98%. After 24 h of reaction, the propane conversion was 39%, the propylene selectivity was 97.8%, and the deactivation rate constant was 0.028 h. -1 .

[0165] The catalysts before and after the reaction in the above examples were tested using high-angle annular dark-field scanning electron microscopy (HAADF-STEM). The catalysts before and after the reaction are shown in the figures below. Figure 11 , 13 As shown, fresh catalyst particles are concentrated at 1.2 nm, while after 24 hours of reaction, the catalyst underwent significant sintering, with particles agglomerating to over 20 nm.

[0166] Test Example 13

[0167] The propane dehydrogenation performance of the C3 catalyst obtained in Comparative Example 3 was determined in a continuous fixed-bed microreactor. Specific conditions were as follows: catalyst dosage 0.1 g, reaction temperature 600 °C, reaction pressure atmospheric pressure, total reaction gas flow rate 30 mL / min (propane 3 mL / min, H2 3 mL / min, nitrogen 24 mL / min). The initial propane conversion rate of the C3 catalyst was 55.6%, and the propylene selectivity was 97%. After 24 h of reaction, the propane conversion rate was 44%, the propylene selectivity was 95.2%, and the deactivation rate constant was 0.019 h⁻¹. -1 .

[0168] Test Example 14

[0169] The propane dehydrogenation performance of the C4 catalyst obtained in Comparative Example 4 was determined in a continuous fixed-bed microreactor. Specific conditions were as follows: catalyst dosage 0.1 g, reaction temperature 600 °C, reaction pressure atmospheric pressure, total reaction gas flow rate 30 mL / min (propane 3 mL / min, H2 3 mL / min, nitrogen 24 mL / min). The initial propane conversion rate of the C4 catalyst was 48.3%, and the propylene selectivity was 70%. After 7 h of reaction, the propane conversion rate was 29.4%, the propylene selectivity was 78.1%, and the catalyst deactivation rate constant was 0.115 h. -1 (like Figure 13 (As shown).

[0170] Test Example 15

[0171] The propane dehydrogenation performance of the C5 catalyst obtained in Comparative Example 5 was determined in a continuous fixed-bed microreactor. Specific conditions were as follows: catalyst dosage 0.1 g, reaction temperature 600 °C, reaction pressure atmospheric pressure, total reaction gas flow rate 30 mL / min (propane 3 mL / min, H2 3 mL / min, nitrogen 24 mL / min). The initial propane conversion rate of the C5 catalyst was 44.5%, and the propylene selectivity was 85.5%. After 7 h of reaction, the propane conversion rate was 32%, the propylene selectivity was 89.5%, and the catalyst deactivation rate constant was 0.076 h⁻¹. -1 (See Table 2).

[0172] Test Example 16

[0173] The propane dehydrogenation performance of the C6 catalyst obtained in Comparative Example 6 was determined in a continuous fixed-bed microreactor. Specific conditions were as follows: catalyst dosage 0.1 g, reaction temperature 600 °C, reaction pressure atmospheric pressure, total reaction gas flow rate 30 mL / min (propane 3 mL / min, H2 3 mL / min, nitrogen 24 mL / min). The initial propane conversion of the C6 catalyst was 59.1%, and the propylene selectivity was 95.1%. After 7 h of reaction, the propane conversion was 37.4%, the propylene selectivity was 92.7%, and the catalyst deactivation rate constant was 0.127 h. -1 (like Figure 14 As shown in Figure 2 and Table 2).

[0174] Test Example 17

[0175] The propane dehydrogenation performance of the C7 catalyst obtained in Comparative Example 7 was determined in a continuous fixed-bed microreactor. Specific conditions were as follows: catalyst dosage 0.1 g, reaction temperature 600 °C, reaction pressure atmospheric pressure, total reaction gas flow rate 30 mL / min (propane 3 mL / min, H2 3 mL / min, nitrogen 24 mL / min). The initial propane conversion of the C7 catalyst was 54.6%, and the propylene selectivity was 95.6%. After 24 h of reaction, the propane conversion was 19%, the propylene selectivity was 96.8%, and the deactivation rate constant was 0.068 h⁻¹. -1 (like Figure 15 As shown in Figure 2 and Table 2).

[0176] Test Example 18

[0177] The propane dehydrogenation performance of the C8 catalyst obtained in Comparative Example 8 was determined in a continuous fixed-bed microreactor. Specific conditions were as follows: catalyst dosage 0.1 g, reaction temperature 600 °C, reaction pressure atmospheric pressure, total reaction gas flow rate 30 mL / min (propane 3 mL / min, H2 3 mL / min, nitrogen 24 mL / min). The initial propane conversion rate of the C8 catalyst was 63%, and the propylene selectivity was 74%. After 8 h of reaction, the propane conversion rate was 43%, the propylene selectivity was 91%, and the catalyst deactivation rate was 0.102 h. -1 (like Figure 16 As shown in the figure and Table 2), the catalyst undergoes significant deactivation during propane dehydrogenation due to the absence of Zn species.

[0178] Table 2: Propane Dehydrogenation Performance of Catalysts

[0179]

[0180] The data in Table 2 indicate that the catalyst prepared in this embodiment exhibits excellent propane dehydrogenation performance. Compared to the catalyst in Comparative Example 1, the catalyst prepared in this invention significantly improves propane conversion, propylene selectivity, and catalyst stability. This is achieved at 600℃ and a propane mass hourly space velocity of 3.54 h⁻¹. -1 Under these conditions, the initial propane conversion rate reached as high as 56.7%, and the propylene selectivity was above 94%. Even after 24 hours of reaction, the propane conversion rate still reached 51.3%, with a deactivation rate of only 0.009 h. -1 It exhibits excellent stability at high temperatures. Characterization results show that after reacting at 600℃ for 24 h, the catalyst metal particles did not sinter, and the carbon deposition was only 3.7 wt.%, demonstrating excellent anti-sintering and anti-carbon deposition properties. It also exhibits high catalytic activity at a lower temperature of 550℃, with an initial propane conversion of 36.4%, a propylene selectivity of 96.7%, and a deactivation rate of only 0.003 h⁻¹. -1 Even without nitrogen dilution, the initial propane conversion at 550°C reached 19.5%, and the initial propylene selectivity was 89%. After 200 h of reaction, the propane conversion remained above 18.1%, and the propylene selectivity reached 93%, exhibiting an extremely low deactivation rate of 0.0004 h. -1 .

[0181] The catalyst provided by this invention exhibits superior catalytic stability compared to the comparative C2-C8 catalysts. The catalysts in Example 2 and the catalysts after the reaction in Example 2 were characterized. Figure 3 and 7It can be observed that the A2 catalyst, after being reacted at 600℃, remains uniformly dispersed as small particles on the support surface, without significant agglomeration. This indicates that the catalyst prepared in this invention has excellent anti-sintering ability during high-temperature reactions.

[0182] The catalyst in Comparative Example C2 and the catalyst after the reaction in Test Example 12 were characterized, such as... Figure 11 , 13 As shown, the control sample C2 catalyst exhibited significant sintering behavior after the reaction, with catalyst particles larger than 20 nm. This further clarifies that the catalyst provided by this invention possesses excellent anti-sintering capabilities.

[0183] Compared with the catalyst of Example 2 and the PtSn / Al2O3 catalyst provided in Comparative Example 7, the catalyst provided by the present invention has a significantly longer service life and excellent long-term stability.

Claims

1. A method for preparing a supported high-entropy Pt catalyst for propane dehydrogenation to propylene, characterized in that: The supported high-entropy Pt catalyst comprises a support and a metallic active component. The support is one or more of silica and alumina. The metallic active component comprises Pt, Zn, Mn, and Al, wherein the Al is at least two of Fe, Co, Ni, Cu, Ga, Ge, In, and Sn. The mass percentage of Pt in the catalyst is 0.1-3 wt.%. The preparation method includes the following steps: S1. A metal precursor salt and a solvent are mixed to obtain a metal precursor salt solution; S2 uses a co-impregnation or stepwise impregnation method to impregnate the metal precursor salt onto the carrier to obtain a mixture; S3 The mixture is dried, calcined and reduced to obtain the supported high-entropy Pt catalyst, wherein the calcination includes heating at a heating rate of 5-20℃ / min; In the catalyst, the atomic percentage of Pt is 5-30%, the atomic percentage of Zn is 5-30%, the atomic percentage of Mn is 10-30%, and the atomic percentage of A is 15-65%.

2. The preparation method according to claim 1, characterized in that: The solvent includes one or more of water, methanol, and ethanol.

3. The preparation method according to claim 1, characterized in that: The carrier is subjected to a drying pretreatment at a temperature of 100-180 ℃ for a time of 1-12 h.

4. The preparation method according to claim 1, characterized in that: The concentration of the metal precursor salt solution is 0.003-0.3 mol / L.

5. The preparation method according to claim 1, characterized in that: The roasting temperature is 300-700 ℃, and the roasting time is 2-6 h.

6. The preparation method according to claim 1, characterized in that: The reduction temperature is 400-800 ℃, and the reduction time is 1-6 h.

7. The application of a supported high-entropy Pt catalyst for propane dehydrogenation to propylene obtained by the preparation method of claim 1 in the propane dehydrogenation to propylene.

Citation Information

Patent Citations

  • High-activity catalyst for propane catalytic dehydrogenation and preparation method thereof

    CN109603821A

  • Method for synthesizing high-entropy alloy nano catalyst, catalyst and application

    CN116809074A